Методологические аспекты оценки стоимости бренда - Нагайская, В. Ю.; Вихляева, Светлана Ивановна (НТУ "ХПИ", 2010)
Представлені сутність і значення поняття "бренд". Розглянуто актуальність проблеми оцінки вартості бренду. Перераховані причини, завдання і переваги для підприємства при проведенні оціночних заходів. Досліджені методи визначення вартості бренду, їх переваги та недоліки.

The main point and the significance of "brand" concept are presented. The actuality of brand cost estimation is considered. The reasons, tasks and advantages of brand estimation measures for enterpriseare are counted. The determination methods of brand cost and their preferences and failings, are investigated.
Keywords: бренд; товарная марка; стоимость актива; методика измерения; финансовая оценка